2015
DOI: 10.1039/c5an01356a
|View full text |Cite
|
Sign up to set email alerts
|

Toward selective, sensitive, and discriminative detection of Hg2+ and Cd2+via pH-modulated surface chemistry of glutathione-capped gold nanoclusters

Abstract: Heavy metal pollution can exert severe effects on the environment and human health. Simple, selective, and sensitive detection of heavy metal ions, especially two or more, using a single probe, is thereby of great importance. In this study, we report a new and facile strategy for discriminative detection of Hg(2+) and Cd(2+) with high selectivity and sensitivity via pH-modulated surface chemistry of the glutathione-capped gold NCs (GSH-Au NCs). By simply adjusting pH values of the colloidal solution of the NCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…QDs with suitable surface ligands are expected to be useful for various applications related to electron and energy transfer , sensing, photocatalysis, and tagging. Among these, designing and development of sensors that have been miniaturized to the nanoscale level can be used for detecting specific target analytes under proper physiological conditions and is an important direction in sensor development research. While several molecule-based sensor systems are developed to detect specific target analytes, only very recently, systems based on QDs are exploited for such a purpose. In this regard, heavy transition metal (HTM) ions are a growing priority because of their build up from different industrial and agricultural activities causing environmental hazards. Ying and co-workers have fabricated CdTe and CdZnSe using glutathione (GSH) ligands and have shown that these systems can be used for the detection of Pb 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QDs with suitable surface ligands are expected to be useful for various applications related to electron and energy transfer , sensing, photocatalysis, and tagging. Among these, designing and development of sensors that have been miniaturized to the nanoscale level can be used for detecting specific target analytes under proper physiological conditions and is an important direction in sensor development research. While several molecule-based sensor systems are developed to detect specific target analytes, only very recently, systems based on QDs are exploited for such a purpose. In this regard, heavy transition metal (HTM) ions are a growing priority because of their build up from different industrial and agricultural activities causing environmental hazards. Ying and co-workers have fabricated CdTe and CdZnSe using glutathione (GSH) ligands and have shown that these systems can be used for the detection of Pb 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhury and co-workers have synthesized CdSeS@ZnS QDs which showed a “Turn-on” response for Pb 2+ and Zn 2+ , while a “Turn-off” response in the case of Cr 3+ ions. Mercury, one of the most prevalent toxic metals found in the environment which permanently damages the central nervous system and the endocrine system leading to deafness, arthritis, etc, is very important to be detected. In this regard, Singhal and co-workers have used CdS QDs capped with glutathione and have shown the signaling event by monitoring the FQ of CdS in the presence of Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, even at very low concentrations, Cd 2+ can induce a wide variety of health issues including the major killer diseases such as heart disease, cancer, and diabetes. [5][6][7][8][9][10] Inevitably, it is highly important to explore efficient methods for monitoring cadmium both in environment and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand Pb 2+ , Hg 2+ and Cu 2+ quenched the PL intensity, which can be overcome by complexing Pb 2+ and Hg 2+ with ammonium fluoride and thiosemicarbazide 44 and Cu 2+ with l -cysteine. 124 Thus, complexing Cu 2+ with l -cysteine prior detection resulted in reduced degree of quenching, demonstrating a possible PL enhancement of the QDs in the presence of common cations. 93 …”
Section: Selective Detection Of Heavy Metal Ionsmentioning
confidence: 94%